Evaluation of the Hydrophilic Complexant N, N, N', N'-tetraethyldiglycolamide (TEDGA) and its Methyl-substituted Analogues in the Selective Am(III) Separation. Issue 5 (29th July 2019) - Klaß, Larissa; Wilden, Andreas; Kreft, Fabian; Wagner, Christoph; Geist, Andreas; Panak, Petra J.; Herdzik-Koniecko, Irena; Narbutt, Jerzy; Modolo, Giuseppe
ABSTRACT: N, N, N', N' -tetraethyldiglycolamide (TEDGA) is used in the French EXAm (extraction of americium) process to separate Am(III) from Cm(III) and Ln(III). In this study, the complexation behavior of TEDGA towards actinides(III) and lanthanides(III) was compared to its methyl-substituted derivatives Me-TEDGA and Me2 -TEDGA under experimental conditions applying to the EXAm process. Using the EXAm solvent, 0.6 mol/L N, N' -dimethyl- N, N' -dioctyl-hexylethoxymalonamide (DMDOHEMA) and 0.45 mol/L bis(2-ethylhexyl)-phosphoric acid (HDEHP), An(III) and Ln(III) distribution ratios increase in the order TEDGA < Me-TEDGA < Me2 -TEDGA. This is explained by differences in the strength of complexation in the aqueous phase: Conditional stability constants for the formation of [Cm(DGA)x ] 3+ complexes decrease in the order TEDGA > Me-TEDGA > Me2 -TEDGA, as shown by time-resolved laser fluorescence spectroscopy (TRLFS). TRLFS measurements verified the exclusive existence of [Cm(DGA)3 ] 3+ complexes in the aqueous phase. Both the homoleptic [Cm(DMDOHEMA)n ] 3+ and the heteroleptic [Cm(DGA)x (DMDOHEMA)y ] 3+ complexes were detected in the organic phase, as postulated in the literature. [14]